การเสริมสร้างความซื่อสัตย์โดยการเรียนรู้ผ่านกรณีศึกษาของนักเรียนชั้นประถมศึกษาปีที่ 4 - จินาศรีพูล, จฤณญา; แสงปัญญา, วีรพล; สุรเศรษฐ, ชุติมา (An Online Journal of Education, 2018)
The research is a Quasi-experimental study. The purpose was to study the effects of honesty enhancement using case-based learning of fourth grade students. The participants comprised 80 fourth grade students from Her Majesty Queen Sirikit 60th Birthday Anniversary School in Changwat Nonthaburi who were enrolled for the 2015 academic year. The participants were allocated to two groups: an experimental group which received honesty enhancement using case-based learning and control group which did not received it. Each group consisted of 40 students. The research instruments were measuring model for honesty and the case-based learning for honesty enhancement of fourth grade students. Data analysis by using means, standard deviations, t-test and repeated measures ANOVA. The results were as follow: 1) Scores of honesty post-test and follow up of the experimental group were significantly higher than their pretest scores at the .05 level of significance. 2) Scores of honesty post-test and follow up of the experimental group were significantly higher than the control group at the .05 level of significance.